2012
DOI: 10.1128/aac.06248-11
|View full text |Cite
|
Sign up to set email alerts
|

Artemisinin-Naphthoquine Combination Therapy for Uncomplicated Pediatric Malaria: a Tolerability, Safety, and Preliminary Efficacy Study

Abstract: dArtemisinin-naphthoquine (ART-NQ) is a fixed-dose coformulated antimalarial therapy recommended as a single-dose treatment and marketed in Papua New Guinea among other tropical countries. We conducted a tolerability, safety, and efficacy study of ART-NQ for Papua New Guinean children aged 5 to 12 years with uncomplicated malaria, comparing single-dose ART-NQ (15 and 6 mg/kg of body weight) given with water (group 1; n ‫؍‬ 15), single-dose ART-NQ (22 and 9 mg/kg) given with milk (group 2; n ‫؍‬ 17), or two dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 24 publications
1
36
0
Order By: Relevance
“…The standard dose of ARCO, which contains 50 mg of naphthoquine and 125 mg of artemisinin per tablet to be given as a single dose of 8 tablets for adults, is equivalent in naphthoquine content to the 800 mg NQAZ treatment tested in this study. Two studies on ARCO that were conducted in Papua New Guinea did not show safety concerns in children (30,31). Although future studies involving larger populations are still needed, these results collectively indicate that NQAZ has an overall good safety profile.…”
Section: Discussionmentioning
confidence: 75%
“…The standard dose of ARCO, which contains 50 mg of naphthoquine and 125 mg of artemisinin per tablet to be given as a single dose of 8 tablets for adults, is equivalent in naphthoquine content to the 800 mg NQAZ treatment tested in this study. Two studies on ARCO that were conducted in Papua New Guinea did not show safety concerns in children (30,31). Although future studies involving larger populations are still needed, these results collectively indicate that NQAZ has an overall good safety profile.…”
Section: Discussionmentioning
confidence: 75%
“…Efficacy against asexual parasite forms over 42 days of follow-up for groups 2 and 3 was 100%, but prolonged gametocyte carriage was observed in some patients (7). The latter observation, together with concerns regarding the emergence of artemisinin resistance in areas of endemicity with a history of subtherapeutic drug use (17), the implication that higher individual pediatric doses than those recommended by the manufacturer can be used, and the safety of the two-dose ART-NQ regimen employed for group 3 (7), supports an argument for a 3-day ART-NQ regimen in line with WHO recommendations for all artemisinin combination therapies (54).…”
Section: Discussionmentioning
confidence: 99%
“…Using either a weight-based equation (28) (7). The regimens used for groups 2 and 3 (means, 9.0 and 9.5 mg/kg NQ per dose) were based on the manufacturer's recommendations of 6.5 to 9.5 mg/kg for children weighing as much as 40 kg (33,38), doses that still fall short of the allometrically scaled dose of Ն10 mg/kg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23,24 To overcome such non-adherence to a repeated dosing regimen, curing malaria patients with a single oral dose of drug is a very important goal. 2526,27,28,29 Toward that goal, we have reported that malaria-infected mice are cured by a single, oral, 6 mg/kg dose of several new artemisinin derivatives combined with 18 mg/kg of mefloquine hydrochloride. 30,31 …”
Section: Introductionmentioning
confidence: 99%